A Study on the Influence of Social Medsia in Digital marketing on Purchase intention of To FMCG Products - et. al., Ms. R.Vidhya , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Social Media is New Platform for promoting the brand, Marketing is very important and it is among the most successful tool and technique in the field of every type of advertising .Social media has rapidly climbed the rungs of the popularity ladder amongst ordinary people during the last few years, so it is very likely that social media will soon surpass all other functional areas of marketing. The Social media is changing traditional marketing communication. Consumers are increasingly using social media to search for information and turning away from traditional media such as television, magazines, radio. etc. The main emphasis in this research is to identify and get insight into the main features of social media ads influencing consumer’s intention to buy. The aim of this research paper was to further understand the area in a measurable way by carrying out empirical research into consumer motivation to shop online. Purchase intentions can be define as an individual’s conscious plan to make an effort to purchase a brand. Purchase intention is an important index for evaluation consumer behavior. The purpose of this study is to investigate the influential factors on Customers’ purchase intention towards social media marketing and how the attitude influences the social media usage pattern.